Effects of an aerobic dance programme on percent body fat in stage one hypertensive adults aged 30-59 - Nahwera, Loyce; Boit, Edwin K.; Nsibambi, Constance A. N.; Maghanga, Mshilla; Wachira, Lucy-Joy (Advances in Health and Exercise, 2024)
Hypertension stands out as a significant concern affecting roughly 1.5 billion individuals globally and is responsible for around 10.8 million premature deaths annually. High percent body fat in humans can contribute to the development of hypertension. The prevalence of hypertension in Uganda is high and it is a major mortality hazard factor for Ugandans. This study aimed to investigate the effects of a 12-week aerobic dance programme on percent body fat in stage one hypertensive adults aged 30-59 in Uganda. This study employed pre-post-test experimental research design. The study participants were randomly assigned to either the experimental group, where a 12-week moderate intensity aerobic dance programme was administered thrice a week for 45 minutes per session, or control group, where no intervention was administered and participants maintained their regular routines. The measurements of percent body fat were done using a Tanita body composition monitor at baseline and post the programme. A paired sample t-test was used to compare mean differences between the two groups. The results for the experimental group indicated that aerobic dance did not lead to a statistically significant reduction in percent body fat (p= 0.472). Similarly, the control group showed no statistically significant reduction (p= 0.520). In conclusion, the aerobic dance programme did not lead to a significant reduction in body fat for this population. However, high body fat remains a risk factor for hypertension. Future studies should explore additional factors, such as dietary influences, to better assess their effects on body composition and hypertension risk.